A generic thermodynamic equilibrium model-based framework for biomass gasification processes - Gan, Gek Hian; Suriyati, Saleh; Noor Asma Fazli, Abdul Samad (Asian Research Publishing Network (ARPN), 2016)
In this paper a generic thermodynamic equilibrium model-based framework for biomass gasification processes has been developed. The designed framework contains a modelling for downdraft and fluidized bed gasifier. A biomass database has been developed as a supporting tools for this framework enabling this framework applicable to study a wide range of biomass gasification processes. Application of this framework has been highlighted based on two objectives. The first objective is to validate the thermodynamic equilibrium model for downdraft gasifier using wood and for fluidized bed gasifier using rice husk respectively. The predicted model shows a good agreement with literature data in terms of gas compositions produced indicating a reliable and valid model is achieved. In addition the performance analysis is performed as a second objective to investigate the optimum parameters for downdraft and fluidized bed gasifiers using wood, rice husk, saw dust and empty fruit brunch. Based on this analysis, the optimum parameters obtained are at temperature 770°C with moisture content of 0.2 and steam biomass ratio 1.32, where the hydrogen gas produced from wood, rice husk, sawdust and empty fruit bunch in downdraft gasifier is 16.38%, 17.02%, 15.11% and 50.12 % respectively, while in the fluidized bed gasifier is 38.75%, 50.12%, 73.24% and 71.77% respectively. The result of the performance analysis shows that the fluidized bed gasifier is more efficient than downdraft gasifier in term of hydrogen gas production.